2015
DOI: 10.21608/eajbsa.2015.12899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lufox on haemolymph and ovarian protein in the soft tick, Argas persicus.

Abstract: Changes in the total protein titer in the haemolymph (HL) and ovaries (Ov) of mated fed normal and Lufox treated female Argas persicus during the reproductive cycle and in the HL of normal male were studied. Tick engorgement was followed by an intial drop of the HL total protein concentration immediately and up to the 2 nd and 3 rd day after feeding (daf), then by a gradual increase on next days to reach maximum on 4-7 and 6-7 daf in the female and male, respectively. The level in the female HL was much higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
4
3
0
Order By: Relevance
“…However, the number of protein fractions in the female HL of the different physiological states examined and their total sum were nearly two times higher in the female (23-24 and 236 fractions) than in male HL (11-12 and 116 fractions) during the whole period of study (unfed, 0-7 and 20 daf). The present results and the higher concentrations of the total protein in the HL of the female A.persicus than in male on 3-7 daf (Radwan et al,2015) are in agreement with findings in previously studied argasids such as A.hermanni (Shanbaky et al,1990 a) and Ornithodoros erraticus (Yousery,2011) and reflect the increasing demands of female argasids for proteins during vitellogenesis.…”
Section: I-native Protein Fractions: I1 Hemolymph (Hl) Protein Fracsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the number of protein fractions in the female HL of the different physiological states examined and their total sum were nearly two times higher in the female (23-24 and 236 fractions) than in male HL (11-12 and 116 fractions) during the whole period of study (unfed, 0-7 and 20 daf). The present results and the higher concentrations of the total protein in the HL of the female A.persicus than in male on 3-7 daf (Radwan et al,2015) are in agreement with findings in previously studied argasids such as A.hermanni (Shanbaky et al,1990 a) and Ornithodoros erraticus (Yousery,2011) and reflect the increasing demands of female argasids for proteins during vitellogenesis.…”
Section: I-native Protein Fractions: I1 Hemolymph (Hl) Protein Fracsupporting
confidence: 93%
“…On 4-7 and 20 daf, the banding patterns increased to 27 patterns with Mwt of 9.51-140.76kD and a number of protein fractions of 20-23 fractions in the different physiological states with a total of 107 fractions during this period (Fig.3b). The evident increase in the numbers of ovary protein fractions on 4-7 and 20 daf conforms to results of the total proteins in A.persicus (Radwan et al, 2015) where their concentration in the ovaries was noticeably increased on the 4 th daf to reach maximal levels on 5-7 daf which followed the maximal levels of the total proteins in the female HL on 4-7 daf. This suggested an uptake and/or increased synthesis of proteins in the ovaries of A.persicus on 4-7 and 20 daf.…”
Section: I2 Ovary Protein Fractions In Female Apersicussupporting
confidence: 85%
See 2 more Smart Citations
“…The level of haemolymph total protein concentration of uninfected O. erraticus females largely decreased immediately after blood feeding and to a lesser extent on the 1 st and 2 nd days after feeding. A similar decrease was observed in the haemolymph of Argas hermanni (Shanbaky et al, 1990a) and Argas persicus (Radwan et al, 2015). This decrease was mainly attributed to dilution of haemolymph during concentration of the ingested blood meal inside the gut (Hefnawy, 1972;Hesse, 1984).Both authors observed an increase in the volume of haemolymph of Argas persicus, Argas arboreus and Ornithodoros moubata for a few days after feeding then the haemolymph volume gradually decreased until oviposition.…”
Section: Total Protein In the Haemolymph Ovary And Eggs Of O Erratisupporting
confidence: 52%